Health Promotion Behaviors of Rural Women with Heart Failure - Carolyn S. Pierce (Rural Nurse Organization; Binghamton University, 2005)
The purpose of this study was to predict the influence of socioecological factors, including social support, barriers to HPB, perceived health status, and demographic variables on the health promotion behaviors (HPB) of rural women with heart failure (HF). A descriptive correlational design was used with a convenience sample of 45 older rural women with HF. Instruments to assess social support, barriers to health promotion, perceived health, and demographic data were utilized. Multiple regression was used to identify sociological influences on HPB, indicating that a significant variance in HPB was predicted by two variables: (1) New York Heart Association classification level (negative association), and (2) a history of diabetes mellitus (DM). Measures of social support, barriers to HPB, and perceived health status were not found to be predictive of HPB.